1995
DOI: 10.1200/jco.1995.13.12.2968
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical and pharmacokinetic study of leucovorin and infusional hepatic arterial fluorouracil.

Abstract: A regimen that combines 5-FU and FA has been identified for regional chemotherapy in patients with hepatic metastases from colorectal cancer. The systemic levels of 5-FU achieved are similar to the conventional IV de Gramont regimen using an identical schedule of 5-FU and FA, which implies that this chemotherapy has the best of both worlds, ie, a regional advantage in delivering high drug concentrations to the target organ with adequate systemic cover for extrahepatic micrometastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…In this way, we hoped to maximize response rates within the liver but also to suppress the development of extrahepatic metastases. It seemed likely that both of these objectives could be achieved; our previous pharmacokinetic and phase I studies showed that high doses of 5-FU could be safely infused intra-arterially and that this regimen produced equitoxic and similar steady-state plasma levels compared with conventional systemic infusional 5-FU (Kerr et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, we hoped to maximize response rates within the liver but also to suppress the development of extrahepatic metastases. It seemed likely that both of these objectives could be achieved; our previous pharmacokinetic and phase I studies showed that high doses of 5-FU could be safely infused intra-arterially and that this regimen produced equitoxic and similar steady-state plasma levels compared with conventional systemic infusional 5-FU (Kerr et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The chemotherapy regimen was based on the results of a previous phase I pharmacokinetic study (Kerr et al, 1995). Folinic acid (200 mg m-2, 10 mg ml-') was infused intravenously over 2 h followed by an intra-arterial loading dose of 5-FU (400 mg m-2, 25 mg ml-1) over 15 min, then 5-FU (1600 mg m-2, 25 mg ml-', plus 4000 j of heparin per g of 5-FU) by intra-arterial infusion over 22 h. This was repeated on day 2 and the 48-h regimen was repeated every 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous leucovorin 400 mg/m 2 over 2 h was followed by a loading dose of 400 mg/m 2 hepatic arterial 5-FU after which 5-FU 1.6 g/m 2 as an hepatic arterial infusion was given over 22 h daily for 2 days, every 2 weeks. A phase I and pharmacokinetic study showed that this regimen produced equitoxic and similar steady-state plasma levels as compared with systemic infusional 5-FU/leucovorin [44]. A subsequent phase II study resulted in a response rate of 46%, and only 29% of patients experienced extrahepatic progression as the first site of relapse [45].…”
Section: Results and Complications Of Hacmentioning
confidence: 99%
“…Dose modification can be performed in accordance with systemic side effects. Since the first-pass hepatic extraction of 5-FU is between 19 and 51%, intra-arterial treatment produces not only high intrahepatic drug levels but also significant systemic levels as a result of nonmetabolized 5-FU that passes the liver [9,24,25].…”
Section: Discussionmentioning
confidence: 99%